Directrices para la realización de los reconocimientos médicos de la gente de mar. - ILO (International Labour Office, 2013)
These Guidelines will assist medical practitioners, shipowners, seafarers' representatives, seafarers and other relevant persons with the conduct of medical fitness examinations of serving seafarers and seafarer candidates.